PENINGKATAN EFISIENSI ANGGARAN BIAYA PRODUKSI DALAM PENGAWASAN BIAYA PADA PT. LANGKAT NUSANTARA KEPONG - Daniel Kelvin Parulian Simanjuntak; Puja Rizqi Ramadhan; Rahima Purba (Ensiklopedia Education Review, 2021)
This research was conducted at PT. Langkat Nusantara Kepong, Where in this study discusses the improvement of the production cost budget planning procedure of PT. Langkat Nusantara Kepong is compiled by each plantation and then reviewed at the main office to ensure that the breakdown of production costs is correct. In general, the plant and technology division is assisted by other divisions in the big office to formulate the expected production amount in the year in question. Then the big office compiles guidelines on production estimation and sends these guidelines together with budget forms to each plantation as a basis for preparing production cost budgets. The plantation production cost budget is then reviewed and re-studied in the big office and coordinated with the administrator of each plantation before it is approved and approved by the company management. Because in preparing the production cost budget, the company uses standard costs. This is good because standard cost prices help companies plan and monitor production costs.Keywords: Budget Efficiency, Production Cost Control, Production Cost Breakdown